Strategi Pengembangan Usaha Kerajinan Keris dalam Meningkatkan Kesejahteraan dan Keberlanjutan Ekonomi di Kabupaten Gianyar - I Made Sara; I Wayan Kartika Jaya Utama; I Made Suniastha Amerta; Pande Putu Mia Dita Sari; Anak Agung Istri Gita Permata Anandra (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This community service activity aims to empower kris craft enterprises in Gianyar Regency by integrating cultural preservation and economic development. The focus is on Sanggar Nami Pusaka, a workshop that produces krises and is dedicated to cultural preservation. The main challenges faced by kris craftsmen include limited managerial and marketing knowledge, restricted market access, and artisan regeneration issues. This craft is often viewed as a traditional activity rather than a sustainable business. Using a Community-Based Empowerment (CBE) approach, the program provides direct assistance in technology implementation and strategic planning, with an evaluation stage to assess the impact and develop a sustainability plan for Nami Pusaka. The program aims to transform Nami Pusaka from a workshop into a more organized business. Through training, the workshop can now access broader markets via digital platforms and improve financial management. The program has led to increased income and strengthened cultural identity, demonstrating that traditional crafts can thrive as a sustainable economic sector. Future recommendations include expanding the program, collaborating with more partners, and focusing on the regeneration of young artisans, with the ultimate goal of global recognition for Gianyar's kris as both a cultural heritage and high-value product.